Peran BAZNAS Sumatera Utara Dalam Menstabilkan Ekonomi Masyarakat Di Tengah Pandemi Covid-19 - Sri Sudiarti; Zainul Fuad; Abdul Fattah (Jurnal Ilmiah Ekonomi Islam, 2022)
The state needs support and collaboration from various parties to support the economic stability of the people directly affected by the Covid-19 pandemic. This study aims to examine the role of BAZNAS North Sumatra in the midst of the Covid-19 Pandemic. This research use desciptive qualitative approach. The result of this research is that Baznas North Sumatra plays an active role in Zakat Collection, Distribution and Utilization of Zakat. The North Sumatra National Amil Zakat Agency's programs in stabilizing the community's economy in the midst of the Covid-19 pandemic include the humanitarian sector (Sumut Peduli), the field of Da'wah Advocacy (Sumut Taqwah), the education sector (Smart Sumatra), the economic sector (Sumut Makmur), the health sector. (Healthy North Sumatra). From the basic programs mentioned during the pandemic, BAZNAS North Sumatra helped a lot in the field of education, such as helping with school fees arrears, the Advocacy Da'wah Sector helping converts to Islam and the economic sector such as productive assistance for business capital assistance. In addition, in the humanitarian field, assistance is in the form of consumptive daily needs and basic necessities.